Pressure measurement and detection of small H2O amounts in high‐pressure H2O–CO2 fluid up to 141 MPa using Fermi diad splits and bandwidths of CO2. (9th March 2020) - Hagiwara, Yuuki; Torimoto, Junji; Yamamoto, Junji
Abstract: Dependence of residual pressures of fluid inclusions on their size and host mineral species provides valuable information related to the depth provenance and P – T – t path of the rocks. Although Raman‐based barometry is an effective method for ascertaining the internal pressure of H2 O–CO2 fluid inclusions, few studies have elucidated Raman spectral features of CO2 in a system of high‐pressure H2 O–CO2 . New experiments using a high‐pressure optical cell in this binary system with compositions of 100, 75 ± 2, and 60 ± 2 mol% CO2 were conducted for this study to verify the availability of Raman CO2 barometers for use in assessing the temperature and pressure conditions of approximately 22°C and 17.3–141.4 MPa. Our results demonstrate that the existence of H2 O does not affect the relation between Fermi diad splits (Δ, cm −1 ) and total pressure of pure CO2 . These results suggest that the Δ–total pressure relation obtained from pure CO2 is also applicable to H2 O–CO2 systems, even at high pressure. However, unlike Δ, because the peak positions of the Fermi diad in the system of H2 O–CO2 shift to a higher wavenumber than those of pure CO2 at given pressure higher than 30 MPa, the peak positions are not very suitable for the pressure scale in an H2 O–CO2 system. Additionally, we confirmed the availability of bandwidths of CO2 as an indicator of compositions that can identify the presence of very small amounts of H2 O (at least 0.3 mol% H2 O), even at room temperature. Abstract : High‐pressure optical cell experiments were conducted in an H2 O–CO2 system at 22°C and 17.3–141.4 MPa temperature and pressure ranges, with samples of bulk compositions of 100, 75, and 60 mol% CO2, to investigate how H2 O affects the CO2 peak positions and shapes. Our results demonstrate that the existence of H2 O does not affect the relation between Fermi diad splits (Δ, cm −1 ) of pure CO2 and total pressure under these experimental conditions.